Educational Triangular Pyramid: A New Concept in Education - Nhung, Trần Văn (VNU Journal of Science: Education Research; Vol 30 No 4, 2014)
Abstract: We believe that one of the most important tasks of education is to establish an organic relationship between family, school, community/society and self-learning in educating a human being as a citizen. In this article an attempt is made to use the concept of triangular pyramid in elementary geometry to illustrate this relationship, emphasizing the fourth element, which is self-learning . These four elements form a quadrilateral in the plane/two-dimensional space, or rather a tetrahedron or a triangular pyramid in three-dimensional space. In fact, all these four elements, their roles and the relationships between them in the process of education and training, and the formation of a man, a citizen, have been studied since ancient time both in Viet Nam and overseas. What is new here may be that the diagram indicating the relationship is illustrated by elementary geometry, specifically by “educational triangular pyramid” . The main idea of this article is derived from [5]. Keywords: Educational triangle, educational triangular pyramid, the relationship between family, school, community/society and self-learning.